Impact of reduced sea ice conditions in the Barents-Kara seas on wintertime atmospheric circulation in the Euro-Atlantic sector - Seidenglanz, Anne (Università Ca' Foscari Venezia, 2019)
The sea ice cover in the Arctic Ocean has experienced an ongoing loss in volume and extent in the last decades with recognised consequences for the northern hemisphere atmospheric circulation. According to climate model projections, this loss is going to continue. Sea ice is an important component of the global climate system as its presence strongly affects the air-sea interaction (via changes in the fluxes of radiative energy, sensible heat, latent heat and momentum) and thus both the atmosphere and ocean. The Barents/Kara (B/K) Seas is the part of the Arctic Ocean experiencing the largest interannual variability and the largest loss in sea ice concentration (SIC) since the start of the observational period. Observational and modelling results point to increased surface heat fluxes from the ocean to the atmosphere, increased surface temperatures, and a reduced meridional surface temperature gradient in response to negative SIC anomalies, with far-reaching effects, including changes in the NAO and the eddy-driven jet stream a few months later. This implies a dual character of the response, from immediate local changes in surface fluxes (affecting atmospheric stability) to a delayed remote response in the atmospheric circulation. On a seasonal time scale, the Arctic sea ice concentration anomalies in autumn influence the winter Euro- Atlantic climate. In particular, recent results suggest a stratospheric pathway in which autumn Arctic sea ice anomalies modify the upward propagating planetary waves that effect the strength of the stratospheric polar vortex, and subsequently determine the tropospheric response in late winter. Here, this mechanism is investigated further using a fully-coupled seasonal prediction system by implementing a negative SIC anomaly in the B/K Seas lasting the whole month of November. This season is chosen because in this time of the year the surface fluxes between ocean and atmosphere are strong and the observed interannual variability in that area is largest. Preliminary results reveal a ...